The Okuru skink (Oligosoma carinacauda sp. nov) of South Westland, New Zealand—simply elusive or extinct? - Bell, Trent; Patterson, Geoff B. (Zootaxa, 2024)
A small brown, longitudinally striped skink from Okuru, South Westland, New Zealand is described as Oligosoma carinacauda sp. nov. It is distinguished from all congeners by the combination of three supraocular scales and a keeled tail. The species is known only from a single specimen, collected from sphagnum moss within supralittoral dune habitat at Mussel Point, Okuru in 2000. Follow-up targeted surveys undertaken since by expert herpetologists have failed to relocate the species to date. As it is known that many New Zealand lizard species face a perilously uncertain future due to anthropogenic-induced pressures such as habitat loss, predatory pests, and climate change, there are serious concerns for the survival of this species.